Effect of Caffeine-Zn2+ System in Preventing Corrosion of Carbon Steel in Well Water - K. Rajam; S. Rajendran; N. Nazeera Banu (Journal of Chemistry)
The inhibition efficiency (IE) of caffeine in controlling corrosion of carbon steel in well water in the absence and presence of Zn2+ has been evaluated by mass loss method. The formulation, consisting of 200 ppm of caffeine and 50 ppm Zn2+, offers 82% inhibition efficiency to carbon steel immersed in well water. Addition of malic acid increases inhibition efficiency of the caffeine-Zn2+ system. The inhibition efficiency of caffeine-Zn2+ and caffeine-Zn2+-malic acid system decreases with the increase in immersion period and increases with the increase in pH from 3 to 11. AC impedance spectra, SEM micrographs, and AFM studies reveal the formation of protective film on the metal surface. The film is found to be UV fluorescent.